UMPH pledges highest integrity and corruption free business practice - UMP, PNC (2019)
UMP Holdings Sdn. Bhd. (UMPH) – the business arm of Universiti Malaysia Pahang (UMP) – recently had its over 300 staff, of various groups and levels of employment, signed an undertaking and pledged their commitment to combat corruption, abuse of power and intra-organization embezzlement.